Skin diseases during floods in Thailand - Vasanop Vachiramon (2018)
Background: Floods are natural disasters that occur occasionally in Thailand. The most common form skin diseases due to floods are infectious dermatoses especially superficial fungal infection. However, the microbiologic evidences have not been evaluated. Objective: To evaluate the most common skin diseases during floods and identify the organism that causes skin maceration at web space(s) of toes (Hong Kong foot). Material and Method: Patients who complained of skin problems were evaluated at the temporary outpatient clinic during October 2006. Skin specimens from all patients who had itches and skin maceration at web space(s) of toes were cultured. Results: Ninety-six patients were evaluated (38 males and 58 females). Eczema was the most prevalent dermatosis, which accounted for 34.5% of the total skin problems and the great majority of these cases were irritant contact dermatitis. Sixteen cases presented with itch and skin maceration at web space(s) of toes. All of them were colonized with various microorganisms. Gram-negative bacilli were the most prevalent ones and were found in 14 out of 16 specimens. Fungal culture was positive in only two specimens. Conclusion: Eczema is the most common dermatosis during floods. Skin maceration at web space(s) of toes, which were thought to be fungal infection, are chronic irritant dermatitis with secondary bacterial colonization. Only a few cases were fungal infection. Microbiologic investigation should be done in these patients. Unfortunately, it is not practical in such a situation. Topical medications that have the combination of antiinflammatory, antibacterial and antifungal properties are the most suitable medications.